TESTING VARIETAL RESPONSE TO VARIOUS FERTILIZER TREATMENTS: PHOSPHORUS, POTASSIUM AND MICRONUTRIENTS ON IMPROVED GROUNDNUT VARIETY (SAMNUT 24) IN AJINGI AND GAYA SAVANNA ZONE OF NIGERIA - SULEIMAN, N.I (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
Groundnut is a leguminous crop that have several applications. This necessitate the search for the application of ways that could improve its production. Field experiments were conducted during the 2015/16 wet season at two locations. The research farm of N2Africa at Ajingi location (Latitude 110. 762238N and Longitude0090.04805E) and Gaya location (110.97570N and longitude 0080. 95753E), the experiment consisted six treatments namely; phosphorus (P), phosphorus +Potassium (PK), Phosphorus + Potassium + Micronutrients (PKM), Phosphorus + Potassium + Micronutrients + Organic Manure (PKMOM), Organic Manure (OM) and Control. The treatments were laid out in a Randomized Complete Block Design (RCBD) with six plots and five replications. P fertilizer (7.5kg) was allocated to plot 1, P (7.5kg) + K in form of MOP at the rate of 20kg K20/ha were allocated to plot 2, p (7.5kg) + K in form of MOP at the rate of 20kg K20/ha were allocated to plot 3, P (7.5kg) + K in form of MOP at the rate of 20kg K20/ha + Organic Manure were allocated to plots four, plot 5 had organic manure and plot 6 control. Soil physico - chemical analysis of the research fields were determined and the metrological data. Data collected on growth and yield parameters (Fresh Weight of Pods, Fresh Weight of Stover, Number of Pods per Plant, Dry Weight of Pods per Plant and Haulms dry weight.) were subjected to analysis of variance (ANOVA) using SAS latest version 2010 and the result indicated that application of all treatment (different fertilizers) combinations significantly (P<0.05) at par showed higher shelling (%) 74.5 % than control 45.1% across plots, locations and at combined analysis.